Implementasi Peraturan Daerah Kota Semarang Nomor 13 Tahun 2013 Tentang Pemberdayaan UMKM di Kecamatan Gunung Pati - REIHA DYAH DEWINDRA; Retno Sunu Astuti (Journal of Public Policy and Management Review, 2018)
Arrangment of small and medium enterprise is a spatial palling set out in Perda Kota Semarang N0. 13 Th. 2013 is motivated by the urge to maintain the function and small-medium enterprise development in Semarang. The purpose if this study is to determine the policy implementation process structuring small-medium enterprise development in sub Gunung Pati using grounding Perda Kota Semarang No. 13 Thn. 2013 on spatial planning Semarang. The result of this study aims to find supporting factors and obstacles that faced by the government in maintaining the function of small-medium enterprise development throught empowerment activities. In this study, researches used the theory of effective implementation of Riant Nugroho to see the implementation process ang implementation of the theory of Van Meter and Van Horn to determine the factors that encourage and hinder the implementation of the policy. This study used qualitatived methods, that using informan from the Dinas Koperasi dan UMKM Semarang, Kecamatan Gunung Pati, and society of sub Gunung Pati itself. The result of this study indicate that the implementation of small- medium enterprise development in sub Gunung Pati. Starting from planning, and controlling. Spacious members of small-medium enterprise in the sub Gunung Pati at 2015 amounted 15% of the total members. Factors that encourage and inhibit this policy is the size and purpose of the policy resources, dispotion implementator, communication between organization, and the economic environment, social and political. This study formulated by a few suggestion that may help the local goverment in Semarang in policy implementation arrangement of small-medium enterprise development in the sub Gunung Pati